2012
DOI: 10.2169/internalmedicine.51.7714
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 Fatty Acids in the Prevention of Atrial Fibrillation Recurrences after Cardioversion: A Meta-analysis of Randomized Controlled Trials

Abstract: Backgroud Previous randomized studies have reported conflicting results on the efficacy of omega-3 fatty acids in preventing atrial fibrillation (AF) recurrences after cardioversion. Objective A systematic review and meta-analysis of the role of omega-3 fatty acids in the prevention of atrial fibrillation recurrences after cardioversion was conducted. Methods PubMed, Cochrane Library, Elsevier, Science Online database were searched up to the end of January 2012 to identify all of the studies in human subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 28 publications
0
11
0
4
Order By: Relevance
“…Other systematic reviews had appraised the evidence on the effects of n‐3 PUFAs to prevent AF 2325,48 with no definitive results, but our analysis, which more than doubled the number of patients and events, precludes any beneficial effects of n‐3 PUFAs for the prevention of secondary and postoperative AF.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Other systematic reviews had appraised the evidence on the effects of n‐3 PUFAs to prevent AF 2325,48 with no definitive results, but our analysis, which more than doubled the number of patients and events, precludes any beneficial effects of n‐3 PUFAs for the prevention of secondary and postoperative AF.…”
Section: Discussionmentioning
confidence: 84%
“…The incorporation of a large and well-conducted clinical trial 47 provided strength to this systematic review, a characteristic that was not present in previous meta-analyses. [23][24][25] Other systematic reviews had appraised the evidence on the effects of n-3 PUFAs to prevent AF [23][24][25]48 with no definitive results, but our analysis, which more than doubled the number of patients and events, precludes any beneficial effects of n-3 PUFAs for the prevention of secondary and postoperative AF.…”
Section: Discussionmentioning
confidence: 85%
“…Some reviews and meta-analyses have demonstrated reductions in adverse events with both plant-based ALA and marine-sourced EPA and DHA supplementation in cardiovascular [9-14,39] and cerebrovascular disease [40], and marine omega-3 PUFA may be effective in preventing atrial fibrillation after cardiac surgery [41,42], although this finding remains controversial [43]. Other reviews have demonstrated mixed [6,15-18] or no benefits [19-21] following marine and/or plant-based omega-3 PUFA supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Накопленные экспериментальные и клинические данные свидетельствуют о прямом антиаритмическом влиянии ПНЖК на кардиомиоциты и плейотропных эффектах в виде уменьшения выраженности окислительного стресса, противовоспалительной и антифибротической активности, которые в своей совокупности, вероятно, опосредуют дополнительный антиаритмический эффект [4,11]. Механизмы антиаритмического и антиокислительного действия ПНЖК взаимосвязаны и включают модификацию системы эйкозаноидов, модификацию состава жирных кислот мембраных фосфолипидов, прямое воздействие неэстерифицированных жирных кислот на миокард, влияние на иннозитол-липидный цикл и сигнальные системы, а также ионные транспортные системы [7,11].…”
Section: Discussionunclassified